2022
DOI: 10.3390/molecules27175654
|View full text |Cite
|
Sign up to set email alerts
|

Transition Metal Catalyzed Hiyama Cross-Coupling: Recent Methodology Developments and Synthetic Applications

Abstract: Hiyama cross-coupling is a versatile reaction in synthetic organic chemistry for the construction of carbon–carbon bonds. It involves the coupling of organosilicons with organic halides using transition metal catalysts in good yields and high enantioselectivities. In recent years, hectic progress has been made by researchers toward the synthesis of diversified natural products and pharmaceutical drugs using the Hiyama coupling reaction. This review emphasizes the recent synthetic developments and applications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 229 publications
0
8
0
Order By: Relevance
“…Furthermore, this method was applied under mild condition and tolerated high functional groups (Scheme 10). [57][58][59] Noor and coworkers 57 suggested the proposed mechanism for Hiyama cross coupling. Analogous to other metal catalyzed cross coupling mechanism, Hiyama cross coupling passed through three steps.…”
Section: Hiyama Cross-couplingmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, this method was applied under mild condition and tolerated high functional groups (Scheme 10). [57][58][59] Noor and coworkers 57 suggested the proposed mechanism for Hiyama cross coupling. Analogous to other metal catalyzed cross coupling mechanism, Hiyama cross coupling passed through three steps.…”
Section: Hiyama Cross-couplingmentioning
confidence: 99%
“…85 Biphenyl benzamide derivatives inhibit the lamenting temperature-sensitive mutant Z (FtsZ) protein, in addition to having antibacterial activities. 87 Firstly, 2,6-diuoro-3hydroxybenzoic acid (56) was alkylated with 3-bromobenzyl bromide (57) in the presence of sodium iodide (KI) and K 2 CO 3 to furnish uorinated acid derivative 58. Then, uorinated acid derivative 58 was reacted with oxalyl chloride (COCl) 2 in the presence of a mixture of dimethylformamide and dichloromethane (DMF/DCM) to afford diuorobenzoyl chloride derivative 59.…”
Section: Suzuki-miyaura Cross-couplingmentioning
confidence: 99%
See 1 more Smart Citation
“…Reactions are typically carried out at high temperatures using DMF, THF, dioxane, DME, or NMP as solvents, and employ a variety of palladium catalysts and ligands. A review published in 2016 summarized the more recent progress in this area, [4] and a 2020 review provided more recent examples, including those using vinyl silanes, as well as other metal catalysts and ligands, and application of microwave [5] . Despite a wealth of literature on the efficacy of arenediazonium salts in metal‐mediated cross‐coupling, [6] there have been little reported work on the use of arenediazonium salts, and aryltriazenes as masked diazoniums, in the Hiyama cross‐coupling, [7] and only few studies on the use of ILs in the Hiyama coupling have been reported [8]…”
Section: Introductionmentioning
confidence: 99%
“…A review published in 2016 summarized the more recent progress in this area, [4] and a 2020 review provided more recent examples, including those using vinyl silanes, as well as other metal catalysts and ligands, and application of microwave. [5] Despite a wealth of literature on the efficacy of arenediazonium salts in metal-mediated cross-coupling, [6] there have been little reported work on the use of arenediazonium salts, and aryltriazenes as masked diazoniums, in the Hiyama cross-coupling, [7] and only few studies on the use of ILs in the Hiyama coupling have been reported. [8] In previous studies, we demonstrated the potential of aryldiazonium salts and aryltriazenes as coupling partners in the Suzuki, Heck, and Sonogashira reactions, employing ionic liquids (ILs) as solvents, in combination with acidic or basic ILs as promoters and catalysts, generating diverse libraries of small molecule building blocks.…”
Section: Introductionmentioning
confidence: 99%